Public Service Motivation and Job Satisfaction among Nurses in Hospitals of Rupandehi District (The Lumbini Journal of Business and Economics, 2021)
Our study examines the effect of public service motivation (PSM) on job satisfaction among nurses during COVID-19 pandemic time in hospitals of Rupandehi district. The structured questionnaire survey was conducted by taking sample of 71 respondents from the hospitals of Rupandehi district. The descriptive research design using correlation and regression was used for the analysis of the data. Out of four dimensions of PSM- three dimensions only were used in the study. Commitment to public interest, self-sacrifice and compassion show positive relationship with job satisfaction. The result shows that PSM exists in nurses and lead to job satisfaction. In COVID pandemic, self-sacrifice dimension of PSM showed significant role for job satisfaction in nurses and other two dimensions (commitment to public interest and compassion) are not significant. This study provides information helpful for hospitals at time of hiring nurses in COVID emergency.